Corporate social responsibility and employee engagement: making the case for international corporate-sponsored volunteering using a matched-sample analysis. Issue 4 (19th August 2021) - Gullekson, Nicole L.; Cedergren, Anders; Arnold, Liz; Brooks, Taggert
Abstract : Purpose: This paper aims to contribute to the growing body of research which demonstrates corporate social responsibility (CSR) initiatives can be linked to individual-level outcomes, such as employee engagement, using a quasi-experimental field study to provide initial evidence of a casual effect for such programs. Design/methodology/approach: The authors examined whether participating in an international corporate-sponsored volunteer program increased employee engagement by comparing a sample of employees, matched on their pre-trip engagement scores and other demographic variables, with employees who did not volunteer in the program and comparing the differences in this employee engagement after completing the volunteer experience. Findings: Using an exact matching technique, the authors were able to isolate the influence of the volunteer program on employee engagement and demonstrate that the program was associated with increased employee engagement after the program ended. Originality/value: This study provides additional, and stronger, support on the CSR and employee engagement relationship through isolating the causal influence of the volunteer program on engagement. Thus, it provides additional justification for the use of, and financial investment in, such programs by organizations.